82.4k views
4 votes
9(y + 6)
find the equivalent expression by using the distributive property

User Hilory
by
5.2k points

2 Answers

4 votes

Answer:

9y+54

Explanation:

Alright we are going to be using the distributive law/Properties

The distributive property states that a(b+c)=ab+ac

So a=9,b=y,c=6

9y+9*6

So you multiply the numbers

9y+54

So therefore, your answer would be 9y+54

User Talha Ashfaque
by
6.1k points
11 votes

Answer:

9y+54

Explanation:

Multiply the number on the outside of the parenthesis with both of the numbers on the inside of the parenthesis.

9*y=9y

9*6=54

Hope this helps!

User P K
by
6.0k points